A review of energy efficient systems integrated into building envelopes - Faizi, M.; Najafi, E.; Khanmohammadi, M.A. (Penerbit Universiti Kebangsaan Malaysia, 2018)
There is an essential need to reduce energy consumption in building sector as it consumes about 40 percent of the world energy and causes environmental problems. About fifty percent of energy in the building sector is used for heating, cooling and air conditioning purposes. Considering building envelopes as particular building elements with many functions which its energetic function is the most important one influencing building energy consumption, enhancing the thermal and energy efficiency of envelopes would decrease energy consumption of the buildings. Building envelopes contain roofs, external walls which are in touch with the outside environment and the floors on the ground. This paper would review a brief history of envelopes evolution and introduce a categorization for the envelopes based on different strategies for enhancing energetic function. A huge literature review on building envelopes has been done to identify different techniques. The result is summarized in five strategies as energy generation, cooling and heating, sun radiation control, and Thermal moderation and adaptive.